The ichnology of shallow-marine and transitional environments - Cónsole Gonella, Carlos (2023)
Fil: Cónsole Gonella, Carlos. Instituto Superior de Correlación Geológica (INSUGEO, CONICET-Universidad Nacional de Tucumán), Avenida Presidente Perón s/n, Yerba Buena, PC 4107, Tucumán, Argentina